Improved Anti-Inflammatory Effect of Silymarin in Rats Induced Liver Carcinogenesis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study aims to Improved Anti-Inflammatory Effect of Silymarin in Rats Induced Liver Carcinogenesis. Silymarin, a flavonolignan isolated from  Silybum marianum, has also been used for centuries as  natural remedy for liver diseases and now reported to have cancer preventive and therapeutic effects . It has been used clinically to treat liver disorders including acute and chronic viral hepatitis, toxin/drug-induced hepatitis and cirrhosis and alcoholic liver disease. The efficacy and dose-response effect of silymarin (125, 250 and 500 mg/kg) were assessed using egg albumin-induced paw edema in rats as a model of acute inflammation. In this model, 56 rats were used and allocated into 7 subgroups each containing 8 rats. All treatments were given intraperitonealy 30 minutes before induction of inflamma tion by egg albumin and then the increase in paw edema was measured 1h, 2h and 3h after induction of inflammation by using the vernier caliper. The results indicated that silymarin, at doses range used, significantly lowered paw edema (P